Early outcomes of posterior cruciate retaining primary total knee arthroplasty in patients of osteoarthritis in Indian population - Dash, Sunil Kumar; Mishra, Sanket; Tripathy, Sumanyu; sharma, Manish; Das, Aurobinda (International Journal of Research in Orthopaedics, 2018)
Background: Total knee replacement arthroplasty today has become the final treatment option for patients with unsalvageable, severely arthritic, painful and deformed knees. In India the numbers of such surgeries are steadily on the rise with bulk of the patients being relatively younger group. Amongst several factors affecting the kinematics of knee, variations in surface geometry and the retention or sacrificing the posterior cruciate ligament is considered especially important. The role of the retaining a PCL on the demographic, clinical and functional parameters of a patient undergoing TKA remains controversial. The aim of the study was to evaluate the outcomes of cruciate retaining primary total knee arthroplasty in patients of osteoarthritis in relation to demographic, clinical and functional parameters. Methods: 20 knees from 12 patients of osteoarthritis including 8 females and 4 males in age group 45-80 years were operated with cruciate retaining implants. The pre and postoperative evaluations were done radiologicaly and clinically using new knee society score. Patients were followed up for minimum 1 year. Results: evaluations of patients revealed good postoperative improvements at subsequent follow up in comparison to preoperative scores. The average range of movement improved by 43.3 degree. The objective, patients satisfaction and functional score improved with scores of 89, 34 and 89.7 at 1 year follow up. The walking distance and staircase climbing, squatting scores also did well. Age did not seem to affect overall outcomes with males having slightly better postoperative scoring overall. Conclusions: In Indian population when the patient is young, high demanding, the retention of cruciate ligaments gives excellent postoperative functionality and objectivity and should be always considered as first choice surgery.